2021
DOI: 10.18632/aging.203308
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting late radiation-induced xerostomia among locoregionally advanced nasopharyngeal carcinoma in intensity modulated radiation therapy era

Abstract: Background: Dry mouth sensation cannot be improved completely even though parotids are spared correctly. Our purpose is to develop a nomogram to predict the moderate-to-severe late radiation xerostomia for patients with locoregionally advanced nasopharyngeal carcinoma (LA-NPC) in intensity modulated radiation therapy (IMRT) / volumetric modulated arc radiotherapy (VMAT) era. Methods: A dataset of 311 patients was retrospectively collected between January 2010 and February 2013. The binary logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In addition, some researchers put forward other different views on TNM stage (15,34,35). By figuring out the C-index value and performing tdROC and DCA, we demonstrated nomogram was more effective on clinical usability compared to the TNM staging system, which was also tested by many previous studies (32,33).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, some researchers put forward other different views on TNM stage (15,34,35). By figuring out the C-index value and performing tdROC and DCA, we demonstrated nomogram was more effective on clinical usability compared to the TNM staging system, which was also tested by many previous studies (32,33).…”
Section: Discussionmentioning
confidence: 69%
“…studies (15,30,31). Considering the AUC value of ROC, the nomogram performed well with a value of 0.7 and was better compared to the 8th TNM staging (32,33). In addition, some researchers put forward other different views on TNM stage (15,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Intensity-modulated radiotherapy (IMRT) is the state-of-the-art method of pinpoint radiation delivery due to recent advancements in radiation equipment and technology 1 . Previous studies [2][3][4][5][6] have shown a significant improvement in IMRT regarding tumor control and quality of life in NPC.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Beetz et al [ 8 ] and Li et al [ 9 ] developed regression models that predict salivary hypofunction using a variety of clinical and demographic information in addition to a DVH-derived mean organ dose in cohorts of size 167 and 365 respectively. Still others have attempted to predict either xerostomia or salivary hypofunction without using any data on the radiation plan [ 10 , 11 ] while others have turned to delta radiomics [ 12 ] for prediction, although these calculations cannot be performed in the radiation planning phase.…”
Section: Introductionmentioning
confidence: 99%